Vibration control of beams under moving loads using tuned mass inerter systems. (15th January 2023) - Zhang, Luqi; Chen, Qingjun; Zhang, Ruifu; Lei, Tuo
Highlights: Ungrounded lightweight TMISs can control moving load-induced beam's vibration. TMIS requires less tuned mass than TMD under the same performance demand. Proposed method can decrease resonant amplitudes under different speeds. Designed robust TMISs are insensitive to changes of parameters and excitations. Abstract: Traditional tuned mass dampers (TMDs) have been proven efficient for the moving-load-induced vibration control of beams. However, a large tuned mass is required in TMDs to adjust the structural dynamic characteristics and achieve the demanded performance targets, which leads to additional dynamic effects and inconvenience of installation. The tuned mass inerter system (TMIS) is an ungrounded lightweight passive control device, which contains a suspended mass, a parallel-connected tuned spring and an inerter-based subsystem. In this study, the application and optimization of TMISs on vibration suppression of multi-span beam models under moving load series are investigated. Using the Bubnov-Galerkin integration method, the modal-superposition generalized system for specified modes of a beam with TMIS under successive moving load series is established. Then, a design strategy for TMISs is proposed to achieve the structural target performance demand by decreasing the moving load-induced resonant responses and attached tuned mass. In the optimization algorithm, the tuned mass ratio is taken as the optimal objective, and the limited dynamic response amplitude under different speed parameters is the constraint condition. A single-span simply supported beam with the TMIS under a moving load series is analyzed. The designed TMISs are tuned to the dominating mode with the maximum mass participate factor of the main structures. TMISs show good vibration mitigation compared to TMDs with equal tuned mass. Meanwhile, under the premise of identical structural performance demands, TMISs require less tuned mass than TMDs and achieve a lightweight control effect. The corresponding dynamic amplitude vs speed curves and time history response curves of beams with TMISs and TMDs are also depicted through comparative analyses. The vertical deflection and acceleration responses apparently decrease, and the resonance is mitigated due to the designed TMISs. The sensitivity analysis results indicate that TMISs attached to beams are insensitive to the perturbance of their parameters and the input moving load excitations; thus, TMIS proves to be a robust tuning system.